SISEF and Italian forest science: thirty years of shared progress - Borghetti M (iForest - Biogeosciences and Forestry, 2025)
Founded in 1995, the Italian Society of Silviculture and Forest Ecology (SISEF) has promoted scientific rigour, inclusivity and collaboration to advance forest sciences in Italy. SISEF supports early-career researchers through initiatives such as its biennial congresses, which provide a platform for scientific exchange and collaboration at national and international levels. Recently, SISEF has expanded its activities to encompass urban forestry and supported the establishment of the AlberItalia Foundation. This foundation focuses on mitigating climate change through nature-based solutions, large-scale tree planting and civic engagement in reforestation and forest stewardship. SISEF has also provided scientific expertise in developing the National Forest Strategy, which was approved in 2022 and provides a framework for sustainable forest management in Italy. Through its platinum open access journals, Forest@ and iForest - Biogeosciences and Forestry, SISEF promotes the dissemination of scientific knowledge. As it marks its thirtieth anniversary, SISEF remains committed to addressing both current and emerging challenges in sustainable forest management, as well as contributing to broader efforts to address climate change.